Vitamin D is an endogenous partial agonist of the transient receptor potential vanilloid 1 channel. (13th August 2020) - Long, Wentong; Fatehi, Mohammad; Soni, Shubham; Panigrahi, Rashmi; Philippaert, Koenraad; Yu, Yi; Kelly, Rees; Boonen, Brett; Barr, Amy; Golec, Dominic; Campbell, Scott A.; Ondrusova, Katarina; et al.
Abstract : Key points: 25‐Hydroxyvitamin D (25OHD) is a partial agonist of TRPV1 whereby 25OHD can weakly activate TRPV1 yet antagonize the stimulatory effects of the full TRPV1 agonists capsaicin and oleoyl dopamine. 25OHD binds to TRPV1 within the same vanilloid binding pocket as capsaicin. 25OHD inhibits the potentiating effects of PKC‐mediated TRPV1 activity. 25OHD reduces T‐cell activation and trigeminal neuron calcium signalling mediated by TRPV1 activity. These results provide evidence that TRPV1 is a novel receptor for the biological actions of vitamin D in addition to the well‐documented effects of vitamin D upon the nuclear vitamin D receptor. The results may have important implications for our current understanding of certain diseases where TRPV1 and vitamin D deficiency have been implicated, such as chronic pain and autoimmune diseases, such as type 1 diabetes. Abstract: The capsaicin receptor TRPV1 plays an important role in nociception, inflammation and immunity and its activity is regulated by exogenous and endogenous lipophilic ligands. As vitamin D is lipophilic and involved in similar biological processes as TRPV1, we hypothesized that it directly regulates TRPV1 activity and function. Our calcium imaging and electrophysiological data demonstrate that vitamin D (25‐hydroxyvitamin D (25OHD) and 1, 25‐hydroxyvitamin D (1, 25OHD)) can weakly activate TRPV1 at physiologically relevant concentrations (100 nM). Furthermore, both 25OHD and 1, 25OHD can inhibit capsaicin‐induced TRPV1 activity (IC50  = 34.3 ± 0.2 and 11.5 ± 0.9 nM, respectively), but not pH‐induced TRPV1 activity, suggesting that vitamin D interacts with TRPV1 in the same region as the TRPV1 agonist capsaicin. This hypothesis is supported by our in silico TRPV1 structural modelling studies, which place 25OHD in the same binding region as capsaicin. 25OHD also attenuates PKC‐dependent TRPV1 potentiation via interactions with a known PKC phospho‐acceptor residue in TRPV1. To provide evidence for a physiological role for the interaction of vitamin D with TRPV1, we employed two different cellular models known to express TRPV1: mouse CD4 + T‐cells and trigeminal neurons. Our results indicate that 25OHD reduces TRPV1‐induced cytokine release from T‐cells and capsaicin‐induced calcium activity in trigeminal neurons. In summary, we provide evidence that vitamin D is a novel endogenous regulator of TRPV1 channel activity that may play an important physiological role in addition to its known effects through the canonical nuclear vitamin D receptor pathway. Key points: 25‐Hydroxyvitamin D (25OHD) is a partial agonist of TRPV1 whereby 25OHD can weakly activate TRPV1 yet antagonize the stimulatory effects of the full TRPV1 agonists capsaicin and oleoyl dopamine. 25OHD binds to TRPV1 within the same vanilloid binding pocket as capsaicin. 25OHD inhibits the potentiating effects of PKC‐mediated TRPV1 activity. 25OHD reduces T‐cell activation and trigeminal neuron calcium signalling mediated by TRPV1 activity. These results provide evidence that TRPV1 is a novel receptor for the biological actions of vitamin D in addition to the well‐documented effects of vitamin D upon the nuclear vitamin D receptor. The results may have important implications for our current understanding of certain diseases where TRPV1 and vitamin D deficiency have been implicated, such as chronic pain and autoimmune diseases, such as type 1 diabetes.